Importance of the enzymatic action of Beauveria bassiana on its pathogenicity toward the reel - CASTELLANOS-DOMÍNGUEZ, OSCAR FERNANDO (Revista Colombiana de Entomología, 1997)
During the last seven years in Colombia the assault of the insect Hypothemenus hampei, called the "reel" to the coffee, has been converted into a serious problem for the national economy. The methods used for its eradication have not offered forceful results, though between them the most effective constitutes the employment of a bioinsecticide obtained from the entomopathogenic fungus Beauveria bassiana. Currently, it is necessary to outline the improvement of the pathogenic properties of the bioinsecticide as of deepest investigations that permit at the same time to visualize all the components of the action of the fungus on the insect. One of the crucial stages in the infection is the enzymatic action of this fungus on the cuticle of the insect. The pathogenicity then can depend on a large extent on this. The knowledge of the particularities of this stage will permit us to elaborate on a better product against the reel. This article is made a detailed justification of the need of deepening in the investigation of the enzymatic action. It is important to take into account certain considerations so as not to fall in untruthful interpretations of the real paper of the enzymes in the pathogenicity, between those which we find: 1. Some parts of the cuticle are more susceptible to enzymatic assault than others, or rather that not only it is important the catalytic activity of the enzymatic complex produced by the fungus or but, furthermore, the specific site of the action of these enzymes in the cuticle; 2. The activity of some enzymes (proteases) is a determinant factor above all in the initial states of the infection, while others (chitinases) are expressed mainly in the late stages of it. 3. Yet it being registered good enzymatic activity, it can be possible that the pathogenicity will be decreased due to the few aggressiveness of the toxins; 4. The action of enzymes is quite cernplex and for the decomposition of each one of the components of the cuticle take part in several enzymes. Because of this, it should be to accomplish a detailed study of the greater number of specific activities to understand which one determines mainly the infectious capacity of the pathogenic agent, for then be able to relate it to the pathogenicity.